Harmonizing Loss Accounting with Local Cultural and Religious Principles - Mohamad, Anwar Thalib; Paputungan , Vindi; Monantun, Widy Pratiwi; Ismail, Ulvarien; Damiti , Fatmawaty (International Journal of Islamic Business and Economics (IJIBEC), 2023)
This research aims to construct loss accounting practices by "binthe biluhuta" sellers based on local wisdom and religious values. This study uses a spiritual paradigm with an Islamic ethnomethodological approach. This approach develops modern ethnomethodology under a secular (interpretive) paradigm. The author conducted observations and interviews with residents to obtain local cultural data. The data obtained was validated using the source triangulation method. The study found that sharing, among others, is a seller's way of avoiding losses. In Gorontalo's Islamic culture, elders often convey these values through advice dilla bo ilaato binthe wawu pale—the meaning of the family statement. The results of this study indicate that the loss accounting implemented by binthe biluhuta sellers is not limited to material things (money) but conditions with local cultural values and faith in the Creator. The theoretical implication of the results of this study is that local wisdom contained in loss accounting implemented by binthe biluhuta sellers can be combined with loss accounting theory to make it more holistic. The concept of loss accounting by binthe biluhuta can be used by sellers with a materialist, humanist, and religious spirit when building a business.